Komunikasi Interpersonal: Faktor Situasional Komunikasi Interpersonal Dalam Perspektif Sosial Exchange, Reinforcement dan Equity - Yusuf Sapari (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
Communication is equalizing the meaning between the two parties between the communicator and communicant. Each has the same function and role when dialogic communication occurs. The communication we do with others has created various forms of communication that exist such as interpersonal communication, persuasive communication, coercive communication and others. This can be seen from the process carried out when the message is delivered to others. Situational and conditional factors in Interpersonal communication can affect a person in communicating with others. This can be seen in the communication process as long as the communication takes place with others. This condition can be analyzed to determine the quality of our communication with others. The process and mechanism of interpersonal communication can be seen from the perspective of the Social Exchange theory, reinforcement theory and Equity theory. From the analysis of various theories, we can find the strengths and weaknesses of Interpersonal communication during the process and the effects that occur after the communication occurs. Keywords: communication, communication process, situational analysis of communication